Cluster-Like Headache Secondary to Sphenoid Sinus Mucocele - Mariana Branco; Rita Rodrigues; Marta Lopes; Luís Ruano (Case Reports in Neurological Medicine)
Background. The great majority of cases of cluster headache (CH) are primary, but there are several reported cases of CH secondary to underlying structural lesions. The identification of these lesions is crucial for the achievement of an effective treatment and favorable outcome, although the determination of a cause-effect relationship between the two entities may be challenging. Case Report. We present the first case of CH secondary to sphenoid sinus mucocele. Discussion. This case reinforces the need to perform neuroimaging studies in CH patients in order to identify lesions that can constitute its cause, especially if atypical features are present. Activation of the trigeminovascular system due to direct contact between the lesion and the trigeminal nerve or by local edema and inflammation possibly plays a role in the pathophysiology of this CH secondary to sphenoid sinus mucocele.